Pengembangan BAM Matakuliah Analaisis Kebijakan Pendidikan Berbasis Online - Supriyanto, Supriyanto; Roesminingsih, Erny; Rifqi, Ainur (Universitas Negeri Surabaya, 2021)
Responding to the development of the Covid-19 virus, the Ministry of Education and Culture, Director General of Higher Education, and State University of Surabaya published a letter related to online learning at home. In order for online learning activities to run smoothly, it is necessary to develop teaching books that are in accordance with the needs of online learning, one of which is in the form of Student Teaching Books (BAM). Based on the results of previous research, BAM has a significant role in learning activities, especially online learning. BAM development is carried out in the Course of Education Policy Analysis using ADD (Analysis, Design, and Development) method. Online learning is implemented using the Google Classroom platform. Based on the results of the analysis carried out, the development of this student teaching book was developed based on 4 aspects, namely aspects of content feasibility, feasibility of presentation of materials, feasibility of language, and feasibility of graphation. The development of this teaching book is validated by 2 experts, namely content experts and linguists. Based on the validation results, the textbook developed obtained a score of 86.5 with excellent assessment criteria, so it is feasible to be a teaching material for students in the Education Policy Analysis Course.